2021
DOI: 10.15302/j-fase-2021386
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Regulation of Climacteric Fruit Ripening: Hormone, Transcription Factor and Epigenetic Modifications

Abstract: • The dynamic interplay between phytohormones plays an important part in climacteric fruit ripening. • Transcription factors are critical for the regulation of climacteric fruit ripening. • Epigenetic modifications act as important regulators of fruit ripening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 218 publications
(362 reference statements)
0
5
0
Order By: Relevance
“…Concerning succinic acid, apricots at harvest treated at T1 had significantly lower, whereas those treated at T2 had a significantly higher content of this acid, compared to the respective control. During the development and ripening of fruit, a succession of plant hormones and their crosstalk occurs (Ji, Xu & Wang, 2021) but the external application of NAs at different times, could cause disruption of natural hormone sequence appearance and thus, alter the content of some metabolic products. After cold storage, all applied treatments had significantly higher succinic acid content than control, while after shelf life the differrences were diminished (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning succinic acid, apricots at harvest treated at T1 had significantly lower, whereas those treated at T2 had a significantly higher content of this acid, compared to the respective control. During the development and ripening of fruit, a succession of plant hormones and their crosstalk occurs (Ji, Xu & Wang, 2021) but the external application of NAs at different times, could cause disruption of natural hormone sequence appearance and thus, alter the content of some metabolic products. After cold storage, all applied treatments had significantly higher succinic acid content than control, while after shelf life the differrences were diminished (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…reported that blueberry had an atypical climacteric ripening process, where a respiratory climacteric character was developmentally regulated by ethylene, but with non-autocatalytic ethylene production during fruit ripening. Except for ethylene, increasing evidence show that other hormones such as auxin, abscisic acid (ABA), brassinosteroids (BRs), gibberellins (GAs), melatonin (MT) and cytokinins (CKs) control fruit ripening ( Ji et al., 2021 ; Kou et al., 2021 ). Other regulatory factors, including epigenetic maintenance and modification and microRNAs, are also involved in fruit ripening regulation ( Liu et al., 2015 ; Fenn and Giovannoni, 2021 ).…”
Section: Ethylene a Key Player In Fruit Ripeningmentioning
confidence: 99%
“…GA works as a negative regulator of fruit ripening, which inhibits the ethylene biosynthesis and perception during fruit ripening of tomato ( Ji et al., 2021 ). SA regulates fruit ripening process mainly through the effect on the expression of ethylene signaling pathway ( Kou et al., 2021 ).…”
Section: Ethylene Interacts With Br Sa Ga Ck and Mt In Regulating Fru...mentioning
confidence: 99%
See 1 more Smart Citation
“…Phytohormones, with different roles in plant growth regulation are being synthetized at different stages of fruit development resulting in regulation of fruit development process [Ji et al 2021]. Exogenous application of natural or synthetic phytohormones as plant growth regulators (PGRs) in fruit production disrupts a normal sequence of phytohormones synthesis resulting in alteration in fruit yield, quality and shelf life [Dias 2019].…”
mentioning
confidence: 99%